PERNIKAHAN DINI DALAM TINJAUAN UNDANG-UNDANG DAN PSIKOLOGI - Ahmad Khoiri (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2020)
The issue of early marriage has always been an interesting material to discuss and debate, because it raises pros and cons from various parties. There have been various responses regarding early marriage, some have responded positively, but few have responded negatively. Early marriage is a social phenomenon that occurs in many parts of the world with different backgrounds. This is certainly a concern of the international community considering the risks arising from early childhood marriages physically and psychologically imperfect as well as sexual relations in early marriage. Poverty is not the only important factor that plays a role in early marriage. When we trace the root of the problem of early marriage in Indonesia, especially on the island of Java, it has actually become something our ancestors did. In their context there is a negative stigma if a woman marries at a mature age in their community. This paper will discuss the phenomenon of early marriage in a legal and psychological context. But not infrequently someone who marries early will experience psychological stress such as stress, irritability, anxiety and depression.